2017
DOI: 10.24095/hpcdp.37.11.03
|View full text |Cite
|
Sign up to set email alerts
|

Between worst and best: developing criteria to identify promising practices in health promotion and disease prevention for the Canadian Best Practices Portal

Abstract: Introduction In health promotion and chronic disease prevention, both best and promising practices can provide critical insights into what works for enhancing the healthrelated outcomes of individuals and communities, and how/why these practices work in different situations and contexts. Methods The promising practices criteria were developed using the Public Health Agency of Canada’s (PHAC’s) existing best practices criteria as the foundation. They were modified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…As outlined in this review, parents are an important avenue for intervention, but to date, the evidence has been limited regarding what types of interventions are effective and should be implemented with parents. Based on the criteria outlined by Fazal et al [32], we have identified four promising interventions [28,42,50,53], all of which relate to aspects of adolescent mental health. Hurley et al [53] demonstrated that a once-off mental health literacy intervention could increase parental mental health help-seeking knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As outlined in this review, parents are an important avenue for intervention, but to date, the evidence has been limited regarding what types of interventions are effective and should be implemented with parents. Based on the criteria outlined by Fazal et al [32], we have identified four promising interventions [28,42,50,53], all of which relate to aspects of adolescent mental health. Hurley et al [53] demonstrated that a once-off mental health literacy intervention could increase parental mental health help-seeking knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Replication of the aforementioned studies with different samples in different contexts is needed to determine if the results of such intervention studies generalize to other populations and situations [32]. Fazal et al [32] indicates that if a promising intervention repeatedly shows it has a positive impact overtime on the desired outcome, it can be deemed best practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of this study, opportunities were defined as an “intervention, program/service, strategy, or policy that shows potential” to improve how ENDS cessation is incorporated into family medicine by addressing a challenge or using practices successfully implemented by the participants. We use this definition so as not to misconstrue these opportunities with best practices which require repeated demonstration of positive impact [ 27 ]. This is in alignment with Nesta’s level one standards of evidence, which states that “you can describe what you do and why it matters, logically, coherently, and convincingly” but not that “you have data that shows positive change [ 28 ].”…”
Section: Methodsmentioning
confidence: 99%